Ghrelin-mediated sympathoinhibition and suppression of inflammation in sepsis - Cheyuo, Cletus (American Physiological Society, 2012)
Sepsis, a systemic inflammatory response to infection, continues to carry a high mortality despite advances in critical care medicine. Elevated sympathetic nerve activity in sepsis has been shown to contribute to early hepatocellular dysfunction and subsequently multiple organ failure, resulting in a poor prognosis, especially in the elderly. Thus, suppression of sympathetic nerve activity represents a novel therapeutic option for sepsis. Ghrelin is a 28-amino acid peptide shown to inhibit sympathetic nerve activity and inflammation in animal models of tissue injury. Age-related ghrelin hyporesponsiveness has also been shown to exacerbate sepsis. However, the mechanistic relationship between ghrelin-mediated sympathoinhibition and suppression of inflammation remains poorly understood. This review assesses the therapeutic potential of ghrelin in sepsis in the context of the neuroanatomical and molecular basis of ghrelin-mediated suppression of inflammation through inhibition of central sympathetic outflow.